(untitled)
This work introduces and examines the concepts of strong β-I -submaximality and strong β-I -paracompactness in ideal topological spaces, presenting them as natural extensions of the classical notions of submaximality and paracompactness. The study emphasizes the analysis of submaximal spaces through the lens of strong β-I -open sets. Additionally, it offers several characterizations of strong β-I -paracompact spaces and investigates the preservation of this property under mappings. , number=3, journal=European Journal of Pure and Applied Mathematics, year=2025, month=Aug., pages=6297